Emergence of amoxicillin resistance and identification of novel mutations of the pbp1A gene in Helicobacter pylori in Vietnam - Trung Thien Tran; Anh Tuan Nguyen; Duc Trong Quach; Dao Thi-Hong Pham; Nga Minh Cao; Uyen Thi-Hong Nguyen; An Nguyen-Thanh Dang; Minh Anh Tran; Loc Huu Quach; Khiem Thien Tran; Nhan Quang Le; Viet Van Ung; et al. (BMC Microbiology, 2022)
Abstract Background Amoxicillin-resistant Helicobacter pylori (H. pylori) strains seem to have increased over time in Vietnam. This threatens the effectiveness of H. pylori eradication therapies with this antibiotic. This study aimed to investigate the prevalence of primary resistance of H. pylori to amoxicillin and to assess its association with pbp1A point mutations in Vietnamese patients. Materials and methods Naive patients who presented with dyspepsia undergoing upper gastrointestinal endoscopy were recruited. Rapid urease tests and PCR assays were used to diagnose H. pylori infection. Amoxicillin susceptibility was examined by E-tests. Molecular detection of the mutant pbp1A gene conferring amoxicillin resistance was carried out by real-time PCR followed by direct sequencing of the PCR products. Phylogenetic analyses were performed using the Tamura-Nei genetic distance model and the neighbor-joining tree building method. Results There were 308 patients (46.1% men and 53.9% women, p = 0.190) with H. pylori infection. The mean age of the patients was 40.5 ± 11.4 years, ranging from 18 to 74 years old. The E-test was used to determine the susceptibility to amoxicillin (minimum inhibitory concentration (MIC) ≤ 0.125 μg/ml) in 101 isolates, among which the rate of primarily resistant strains to amoxicillin was 25.7%. Then, 270 sequences of pbp1A gene fragments were analysed. There were 77 amino acid substitution positions investigated, spanning amino acids 310–596, with the proportion varying from 0.4 to 100%. Seven amino acid changes were significantly different between amoxicillin-sensitive (AmoxS) and amoxicillin-resistant (AmoxR) samples, including Phe366 to Leu (p <  0.001), Ser414 to Arg (p <  0.001), Glu/Asn464–465 (p = 0.009), Val469 to Met (p = 0.021), Phe473 to Val (p <  0.001), Asp479 to Glu (p = 0.044), and Ser/Ala/Gly595–596 (p = 0.001). Phylogenetic analyses suggested that other molecular mechanisms might contribute to amoxicillin resistance in H. pylori in addition to the alterations in PBP1A. Conclusions We reported the emergence of amoxicillin-resistant Helicobacter pylori strains in Vietnam and new mutations statistically associated with this antimicrobial resistance. Additional studies are necessary to identify the mechanisms contributing to this resistance in Vietnam.